Dividend Payment Procedure in Joint Stock Companies of EU Countries And their Tax Mechanism (European Journal of Economics, Finance and Business Development, 2024)
In this article, dividend policy, approaches to dividend payment, dividend payment procedure, general requirements for dividend policy, activity of agents in dividend policy and their necessity are highlighted. An analysis of the level of tax rates levied on dividend income in EU countries is also provided.